Therapeutic Communication Skills for Nurses - ช. ดูวอล อัญชลี; ทุมเสน ตติยา (Journal of The Royal Thai Army Nurses, 2019)
Communication is essential in nursing practice. This article submits the concept of communication in brief. It also tries to focus on the nurses’ role in striking up therapeutic relationship with their clients, and the concept of “Therapeutic communication” as well as highlight its importance in clinical practice for nurses, that can encourage clients to express feelings and ideas about their health status and problems, which could consciously influence individual contemplation of behavioral changes. The context in each part of this article illustrates various communication techniques that are not only stimulate expression of individual’s thoughts and feelings, but also enhancing awareness. Moreover, nurses can practice therapeutic communication skills from the case studies presented in this article as well.